CORN SILK TEA EXTRACT AS ANTIDIABETIC : A REVIEW - Ila Maratush Shalihah; Vega Yoesepa Pamela; Septariawulan Kusumasari (Food ScienTech Journal, 2020)
Diabetes Mellitus type 2 usually occurs in people who are overweight and have less physical movement. Usually, that disiease triggers by sedentary lifestyle. Patients with diabetes mellitus are characterized by high blood glucose levels (hyperglycemia) due to a lack of insulin secretion, insulin action, or both. Decreasing blood sugar levels can be done in several ways, namely by diet and consumption of drugs. One of the efforts to help speed up diabetes treatment is to consume corn silk tea. Corn silk is one part of corn that has not been fully utilized and contains flavonoids, which are believed to reduce blood glucose levels. Flavonoids in corn silk reduce blood glucose levels by stimulating insulin secretion by pancreatic β cells, activating insulin receptors, and repairing damaged pancreatic β cells through antioxidant activity; flavonoids also inhibit the breakdown of carbohydrates. The process of making corn silk tea can be done in several procedures. Before making, corn silk can be dried or not dried; making the extract can be boiled for a long time or only for a short time. The difference in the manufacturing process affects the tea content and its effect on blood sugar levels. Corn silk tea that has been formulated to be drunk regularly in a repetition can reduce blood sugar levels in respondents with high blood sugar levels.